2023
DOI: 10.37190/ppmp/166008
|View full text |Cite
|
Sign up to set email alerts
|

Quinic acid as a novel depressant for efficient flotation separation of scheelite from calcite

Abstract: There are difficulties to the conventional depressant for achieving separation of scheelite from calcite for the sake of their similar surface properties. The paper reported that a new depressant quinic acid (QA) was used for separating scheelite from calcite. The adsorption experiments, zeta potential experiment, contact angle, FTIR, XPS analysis and crystal chemistry analysis were utilized to known the depression mechanism of selectivity. The results showed that the recovery of calcite decreased drastically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…For calcite, as for another significant Ca-bearing mineral apart from fluorite, flotation reagent quantum chemistry studies have also been reported. For instance, Zhang et al [224] employed PA-Na as a calcite depressant and investigated its depression mechanism during the selective flotation of scheelite from calcite using microflotation experiments, zeta potentials, XPS, and DFT calculations. The results demon-Figure 6.…”
Section: Other Calcium-bearing Mineralsmentioning
confidence: 99%
See 1 more Smart Citation
“…For calcite, as for another significant Ca-bearing mineral apart from fluorite, flotation reagent quantum chemistry studies have also been reported. For instance, Zhang et al [224] employed PA-Na as a calcite depressant and investigated its depression mechanism during the selective flotation of scheelite from calcite using microflotation experiments, zeta potentials, XPS, and DFT calculations. The results demon-Figure 6.…”
Section: Other Calcium-bearing Mineralsmentioning
confidence: 99%
“…For calcite, as for another significant Ca-bearing mineral apart from fluo-rite, flotation reagent quantum chemistry studies have also been reported. For instance, Zhang et al [224] employed PA-Na as a calcite depressant and investigated its depression mechanism during the selective flotation of scheelite from calcite using micro-flotation experiments, zeta potentials, XPS, and DFT calculations. The results demonstrated that PA-Na is able to chemisorb on both calcite (104) and scheelite (111) surfaces, but the absolute value of the adsorption energy of PA-Na on the calcite surface is larger than that on the scheelite surface, revealing that the use of PA-Na can depress calcite more easily in the flotation separation of calcite from scheelite.…”
Section: Other Calcium-bearing Mineralsmentioning
confidence: 99%